The Impact of Tobacco Use on Preterm Premature Rupture of the Membranes - Andres, Robert L.; Zhao, Yuan; Klebanoff, Mark A.; Hauth, John C.; Caritis, Steve N.; Carey, J. Christopher; Wapner, Ronald J.; Iams, Jay D.; Leveno, Kenneth J.; Miodovnik, Menachem; Sibai, Baha; Van Dorsten, J. Peter; Dombrowski, Mitchell P.; O'Sullivan, Mary J.; Langer, Oded; null (American Journal of Perinatology, 2013)
Objective To determine if tobacco use increases the incidence of preterm premature rupture of the membranes (pPROM) or alters perinatal outcomes after pPROM.Study Design This is a secondary analysis of the databases of three completed Eunice Kennedy Shriver National Institute of Child Health and Human Development–supported Maternal Fetal Medicine Units Network studies. Self-reported tobacco exposure data was obtained. Its relationship with the incidence of pPROM and associated neonatal outcome measures were assessed.Results There was no difference in the incidence of pPROM when comparing nonsmokers to those using tobacco. Although a trend was seen between the incidence of pPROM and the amount smoked, this did not reach statistical significance. Among the patients with pPROM, the use of tobacco was not associated with an increase in perinatal morbidity.Conclusion Our data do not support a significant relationship between tobacco use and pPROM.
Keywords: tobacco; premature rupture of the membranes